Enhanced Ciprofloxacin Removal from Aqueous Solution Using a Chemically Modified Biochar Derived from Bamboo Sawdust: Adsorption Process Optimization with Response Surface Methodology. (31st July 2022) - Wakejo, Wondimu K.; Meshasha, Beteley T.; Kang, Joon W.; Chebude, Yonas
Abstract : Contamination of water by ciprofloxacin has become a significant concern due to its adverse health effects and growing evidence of antimicrobial-resistant gene evolution. To this end, a chemically modified bamboo biochar was prepared from bamboo sawdust to effectively remove ciprofloxacin (CIP) from an aqueous solution. Under similar adsorption conditions, the modified bamboo biochar (MBC) has an excellent CIP removal efficiency (96%) compared to unmodified bamboo biochar (UBC) efficiency (45%). Thus, MBC was used in batch adsorption experiments, and the process was optimized with the central composite design (CCD) framework of response surface methodology (RSM). Sorption process parameters such as initial CIP concentration, pH, adsorbent dose, and contact time were studied and found to have a significant effect on CIP removal. The optimal CIP removal (96%) was obtained at MBC dose (0.5 g L -1 ), CIP initial concentration (20 mg L -1 ), pH (7.5), and contact time (46 min). The adsorption kinetic data were well described by the pseudo-second-order model (R 2 = 0.999 ), and both Langmuir (R 2 = 0.994 ) and Freundlich (R 2 = 0.972 ) models gave the best fit in CIP adsorption isotherm analysis. The maximum monolayer adsorption capacity of the MBC was 78.43 mg g -1 based on the Langmuir isotherm model. These results suggest that CIP adsorption was mainly controlled by chemisorption. Moreover, the CIP adsorption process was endothermic and spontaneous. Overall, MBC is a low-cost, efficient, and recyclable adsorbent for eliminating emerging contaminants such as ciprofloxacin from an aqueous solution.